The Impacts of Sectional Speed Control and Dynamic Speed Management on Traffic Safety on Motorways – The Evidence Across the EU and the Impact Estimation for Slovenia - ZANNE, Marina; TÖRÖK, Adam (Promet - Traffic&Transportation, 2026)
Road safety remains a pressing issue worldwide. In Europe, many countries are following the “Vision Zero” strategy, a concept developed in Sweden in the early 1990s, based on the conviction that road deaths can be systematically prevented. Speed is still one of the main causes of traffic accidents. Studies show that the risk of a fatal accident doubles with an increase in speed of just 15 km/h, which has led to numerous measures to reduce speed in various road categories. This article examines the effects of sectional speed control and dynamic speed management on road safety on motorways. Sectional speed control calculates the average speed of a vehicle over a given distance, while dynamic speed management adapts speed limits to traffic and environmental conditions in real time. Although these methods have been implemented successfully in several countries, Slovenia plans to introduce them in the second half of 2025. Based on a review of the relevant literature and existing case studies, this paper assesses the expected benefits for traffic safety on Slovenian motorways. Slovenia’s unique context, characterised by its transit location and significant daily interregional migration, results in strong and heterogeneous traffic flows on its motorways and deteriorated traffic safety on these roads.